BS EN 15655-2. Ductile iron pipes, fittings and accessories. Requirements and test methods for organic linings of ductile iron pipes and fittings. Part 2. Thermoplastic Modified Polyolefin (TMPO) lining of pipes (16th December 2019) - British Standards Institution,
No abstract available